(3GdHjGJ aj GdEQK hGdJhQjKGJs - (3GdYGedj, CHh YHO Gddg, LdGd GdOjf, eMeO Hf ecj Hf TeS GdOjf Hf eMeO VjGA GdOjf, ef PQjI GdTgjO GdChd eMeO Hf ecjs ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPQj CQTOfG HOjf GdESdGe (B... (3cJGH GdaQGFV hGHhGHg KdGKI GdChd aj GdebOeGJ, hajg aUhd GdChd aj ehLH GdEQK, EfeG jKHJ GdEQK HCeQjf fSH hSHHs
(3BNQgG (B:s
(3CNQgG(B: (3GKfGf hKdGKhf dCfgG GfcSQJ aj eNQL GdQHY aJVQH CQHYI aj CUd GdaQjVI hgj KeGfjI JHdZ GKfjf hKdGKjf hGdSge GdRGFO jDNP ef GdLejY ajchf KdGKI hKdGKjf(B. (3hgPG BNQ GdQSGdIs
(3Je PcQ GdfGSN hJGQjN GdfSN GYJeGOG Ydi GdPQjYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B3: 107s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis